Chronic catatonia treated with electroconvulsive therapy: a case report - De Silva, V.A.; Lakmini, W.D.; Gunawardena, H.N.; Hanwella, Raveen (Springer Nature, 2013)
Introduction: In the International Statistical Classification of Diseases and Related Health Problems 10 and Diagnostic and Statistical Manual of Mental Disorders IV classification systems, catatonia is classified as a subtype of schizophrenia. However, catatonia is more frequently associated with mood disorders than schizophrenia. It is also associated with organic conditions. Catatonia responds to treatment with benzodiazepines and electroconvulsive therapy rather than antipsychotics. These features support the categorization of catatonia as an independent syndrome. There is a lack of consensus regarding the definition of chronic catatonia. There are two previous case reports of effective treatment of chronic catatonia with electroconvulsive therapy. Case presentation: A 29-year-old South Asian woman was admitted to hospital because of poor food intake. Her condition had progressively worsened over the past seven months. She had features of catatonia. On admission, her Bush-Francis Catatonia Rating Scale score was 24. Her symptoms resolved after the administration of 17 electroconvulsive therapies but recurred later. She was given a further four electroconvulsive therapies. She remains well on aripiprazole at a dose of 60mg a day. Conclusions: Bilateral electroconvulsive therapy is effective in the treatment of chronic catatonia and should be considered as a treatment option. A relapse of symptoms can occur after the discontinuation of treatment.
Keywords: Chronic catatonia; Electroconvulsive therapy; Schizophrenia